Candidiasis Mucocutánea Crónica. Estudios inmunológicos y tratamiento específico con factor de transferencia. Reporte de un caso clínico - Patrucco, Raúl (1978)
We report the case of case of a 11 -years old gril with Chronic Mucocutaneous Candidiasis since two months of age, involving skin, sclap, nails and mucous membranes, persistent after several treatments with amphotericin B. The special immunologic studies revealed negative candidine, PPD and 2-4-DNCB skin test reactions, impaired response of lymphocytes to stimulation in vitro witch candida antigen and low number of rosette-forming T lymphocytes in peripheral blood. Titers of antibodies anti-candida were very high in serum and saliva and the phagocytic activity of macrophages was normal. After treatment with Trasnfer Factor derived from nomal lymphocytes, clinical remission and improvement of the immunological reactivity occured.